Cyclic drying and wetting tests on combined remediation of chromium-contaminated soil by calcium polysulfide, synthetic zeolite and cement - Xilin Li (Nature Portfolio, 2021)
Abstract Using calcium polysulfide as the reducing agent, synthetic zeolite as the adsorbent, and cement as the curing agent, the dual-index orthogonal test method was used to determine the best remediation dosage of chromium-contaminated soil. On this basis, through the dry–wet cycle test, the durability of the chromium-contaminated soil after repair is analyzed from the perspectives of unconfined compressive strength, toxic leaching concentration, quality loss, and microscopic characterization. Test results showed that the optimal ratio for the joint repair of chromium-contaminated soil was 3 times the amount of CaS5, 15% synthetic zeolite, and 20% cement. With the increase in the number of wet–dry cycles, the unconfined compressive strength of the composite preparation combined to repair chromium-contaminated soil was first increased and then reduced, and the concentration of Cr(VI) and total chromium in the leachate was first decreased and then increased. The higher the chromium content of the contaminated soil was, the lower the unconfined compressive strength, and the higher the leaching concentration of Cr(VI) and total chromium were. With the increase in cycle times, the cumulative mass-loss rate of composite preparations for repairing chromium-contaminated soil gradually increased, and the higher the chromium content was, the higher the cumulative mass-loss rate, which was less than 2%, reflecting the combination of composite preparations for repairing chromium-contaminated soil to have good durability. Microscopic and macroscopic results are consistent with each other.